2009
DOI: 10.1371/journal.pone.0004284
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin Ligase RPM-1 and the p38 MAPK PMK-3 Regulate AMPA Receptor Trafficking

Abstract: Ubiquitination occurs at synapses, yet its role remains unclear. Previous studies demonstrated that the RPM-1 ubiquitin ligase organizes presynaptic boutons at neuromuscular junctions in C. elegans motorneurons. Here we find that RPM-1 has a novel postsynaptic role in interneurons, where it regulates the trafficking of the AMPA-type glutamate receptor GLR-1 from synapses into endosomes. Mutations in rpm-1 cause the aberrant accumulation of GLR-1 in neurites. Moreover, rpm-1 mutations enhance the endosomal accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
77
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(86 citation statements)
references
References 59 publications
6
77
2
1
Order By: Relevance
“…We found that MYCBP2-deficiency causes constitutive p38 MAPK activation which, surprisingly, prevented activity-induced internalization of the transient receptor potential vanilloid receptor 1 (TRPV1). This finding contrasts the role of MYCBP2 and p38 MAPK in AMPA receptor internalization in C. elegans (14) as well as the previously described role of p38 MAPK in promoting receptor internalization in mammalians (18 -20). Thus, our findings suggest that p38 MAPK fulfills receptor-dependent versatile roles in the regulation of receptor internalization.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…We found that MYCBP2-deficiency causes constitutive p38 MAPK activation which, surprisingly, prevented activity-induced internalization of the transient receptor potential vanilloid receptor 1 (TRPV1). This finding contrasts the role of MYCBP2 and p38 MAPK in AMPA receptor internalization in C. elegans (14) as well as the previously described role of p38 MAPK in promoting receptor internalization in mammalians (18 -20). Thus, our findings suggest that p38 MAPK fulfills receptor-dependent versatile roles in the regulation of receptor internalization.…”
contrasting
confidence: 99%
“…However, p38 MAPK activation has been demonstrated to promote internalization of -opioid-and AMPA receptors which would be in contrast to our findings (14,18,20,34). Therefore, we tested in the next step whether or not p38 MAPK-activation prevents TRPV1 internalization in MYCBP2-deficient neurons.…”
Section: Generation Of Mice With Mycbp2 Deficiency In Nociceptivecontrasting
confidence: 76%
See 1 more Smart Citation
“…Park et al (2009) found that RPM-1 regulates AMPA receptor trafficking in interneurons in C. elegans. RPM-1 works by negatively regulating the levels of DLK-1 (MAPKKK) (Park et al 2009). …”
Section: E3smentioning
confidence: 99%
“…RPM-1 negatively regulates the MAP kinase pathway of MAPKKK DLK-1, MAPKK MKK-4 and p38 MAPK PMK-3. Recently, this pathway was shown to also regulate trafficking of the AMPA-type glutamate receptor GLR-1 (Park et al, 2009). Destabilization of enhancer binding protein CEBP-1 mRNA has also recently been shown to alter local translation of MAPKKK components in distal axons to disrupt axon morphology and synapse formation in C. elegans (Yan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%